Sacred Privacy - Yildirim, Gulumhan H. (Tufts Archival Research Center, 2019)
I am interested in culture, identity, space, and how they interact with each other. My thesis is about building private spaces within public spaces such as university buildings. While the project initially emerged as a response to my religious needs on an individual level, it later evolved into a bigger question on a social level. I attempt to reverse the conversation about Muslims who are associated only with terrorism. Islamophobia and xenophobia have been on rise in the past few years as the growing numbers of attacks on mosques prove.